Ju/’hoansi Survival in the Face of HIV: Questions of Poverty and Gender - Susser, Ida (Anthropologica, 2022)
Both the debate around poverty among the Kalahari San and the discussions of gender autonomy are significant for identifying possibilities for prevention of HIV/AIDS among contemporary Ju/’hoansi. This paper discusses field work with respect to HIV/AIDS conducted by Richard Lee and myself in Ju/’hoansi villages in Namibia and Botswana in 1996, 1997, 1999 and 2001. Our findings suggest variation in the experiences of both poverty and gender among the different villages which may have implications for the prevention of HIV/AIDS. In the villages where people still constructed simple, moveable homes from clay and branches and foraging was still a possibility, women and men expressed more stable views of their relationships and women seemed to maintain a degree of power and independence in marriage. In contrast, poverty and the disintegration of households seemed markedly manifest in villages which served as administrative and market centres and where most of the population lived in brick houses and had little access to a foraging subsistence